Letter from the President: Fall / Winter 2025 (The Advocate, 2025)
ATE-K President Dr. Amanda Lickteig invites and introduces readers to the four articles found in the Fall/Winter 2025 issue of The Advocate. She also invites participation in the upcoming 2026 conference in Manhattan, KS on March 27, 2026.